Dietary lutein plus zeaxanthin and choline intake is interactively associated with cognitive flexibility in middle-adulthood in adults with overweight and obesity. (3rd July 2022) - Edwards, Caitlyn G.; Walk, Anne M.; Thompson, Sharon V.; Reeser, Ginger E.; Dilger, Ryan N.; Erdman, John W.; Burd, Nicholas A.; Holscher, Hannah D.; Khan, Naiman A.
ABSTRACT: Background: The xanthophyll carotenoids lutein+zeaxanthin and the dietary component choline have been linked to benefits in cognition. However, knowledge on the interactive influence of these dietary components on cognitive function is sparse. Design: 80 middle-aged adults with overweight and obesity (Body Mass Index: (BMI) ≥25.0 kg/m²), completed 7-day diet records, venous blood draws, heterochromatic flicker photometry, assessment of intelligence quotient (IQ), and a cognitive flexibility task while undergoing electroencephalographic recording for event-related potential (ERP) extraction. Multiplicative interaction terms and hierarchical linear regressions, controlling for age, BMI, sex, annual household income, and IQ were utilized to assess independent and interactive contributions of dietary and biomarker data on Switch task outcomes. Results: Higher intake of lutein+zeaxanthin and choline was associated interactively, but not independently, with faster reaction time (RT), after controlling for pertinent covariates. Dietary intake of lutein+zeaxanthin and choline was associated with serum lutein concentrations, but not with plasma choline metabolites nor macular pigmentation. Plasma phosphatidylcholine (PC) concentrations were associated with higher accuracy in Switch trials, while no other biomarkers were associated with cognitive outcomes. Dietary intake and biomarker data were not related to the N2 nor P3 ERP component. Conclusions: Among a sample of adults with overweight and obesity, greater intake of choline and lutein+zeaxanthin was associated with faster performance on a cognitive flexibility task. Future work examining methods of increasing consumption of both of these dietary components as a possible means of improving or maintaining cognitive flexibility among adults with overweight and obesity is therefore warranted.